2006
DOI: 10.3201/eid1205.051424
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus Infection, Canada

Abstract: Human Bocavirus was detected in 18 (1.5%) of 1,209 respiratory specimens collected in 2003 and 2004 in Canada. The main symptoms of affected patients were cough (78%), fever (67%), and sore throat (44%). Nine patients were hospitalized; of these, 8 (89%) were <5 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
216
12
22

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(280 citation statements)
references
References 16 publications
30
216
12
22
Order By: Relevance
“…Although IgG antibody present in a single serum sample does not reflect an acute infection, a high rate of IgG positive sera from healthy children does suggest that HBoV infection is more common in children than genomic detection has shown previously (Allander et al, 2005;Arnold et al, 2006;Bastien et al, 2006;Choi et al, 2006;Foulongne et al, 2006;Lin et al, 2007;Ma et al, 2006;Qu et al, 2007;Sloots et al, 2006;Weissbrich et al, 2006). Infection with B19 occurs in children in a high incidence asymptomatically.…”
Section: Discussionmentioning
confidence: 91%
“…Although IgG antibody present in a single serum sample does not reflect an acute infection, a high rate of IgG positive sera from healthy children does suggest that HBoV infection is more common in children than genomic detection has shown previously (Allander et al, 2005;Arnold et al, 2006;Bastien et al, 2006;Choi et al, 2006;Foulongne et al, 2006;Lin et al, 2007;Ma et al, 2006;Qu et al, 2007;Sloots et al, 2006;Weissbrich et al, 2006). Infection with B19 occurs in children in a high incidence asymptomatically.…”
Section: Discussionmentioning
confidence: 91%
“…According to the literature, the prevalence of hBoV infection among hospitalized children with respiratory tract infection ranges between 1.5-18.3% (Bastien et al 2006, Kaplan et al 2006, Allander et al 2007). In our study, we found a prevalence of 13.2%, which is one of the highest reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Human parvovirus B19, the only other parvovirus that is pathogenic to humans, is also seasonal, with peak occurrences in spring and summer (Heegaard & Brown 2002). Bastien et al (2006) observed no seasonal prevalence, which may be reflected by the low prevalence in their study (Bastien et al 2006). Nonetheless, as highlighted by Schildgen et al (2008), it is very difficult to draw any definitive conclusion on the seasonal distribution of a new viral agent based only on analyses of a single season because there is much variation of the peak respiratory season from year-to-year (Schildgen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…PCR is the most common method used to detect acute infections of HBoV1 (Bastien et al, 2006;Kesebir et al, 2006;Allander et al, 2007;Fry et al, 2007;Schildgen et al, 2008). However, HBoV1 DNA has been shown to remain detectable by PCR in respiratory samples for several months after primary infection (Brieu et al, 2008;Blessing et al, 2009;Lehtoranta et al, 2012;Martin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%